A Novel Virtual Voltage Comparison Compensation for Dynamic Voltage Restorer. (25th May 2022) - Xu, Jie; Niu, Pengcheng
Abstract : In view of the high-quality requirements of the power supply quality of the user-side sensitive equipment, the system for voltage sag in the grid operation is stable and efficient. This paper proposes a new virtual voltage comparison compensation dynamic voltage recovery method. The algorithm that uses the invariant constant signal as the input quantity, and the real-side input load side signal reduces the influence of the input quantity uncertainty change on the generated compensation signal and improves the simplicity of the system operation control and the system stability. The flexibility of the proposed control strategy, as well as the effectiveness of the optimal design method, is verified by both simulation and experimental results.